2012
DOI: 10.1682/jrrd.2010.07.0125
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study to develop telehealth tinnitus management for persons with and without traumatic brain injury

Abstract: Abstract-Tinnitus, or "ringing in the ears," affects 10%-15% of adults; cases can be problematic and require lifelong management. Many people who have experienced traumatic brain injury (TBI) also experience tinnitus. We developed Progressive Tinnitus Management (PTM), which uses education and counseling to help patients learn how to self-manage their reactions to tinnitus. We adapted PTM by delivering the intervention via telephone and by adding cognitive-behavioral therapy. A pilot study was conducted to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 51 publications
1
26
0
1
Order By: Relevance
“…In examining the severity of the symptoms captured using PROMs, over half of the mTBI participants who reported hearing loss had an HHIA sore classified as significant, emphasizing the impact hearing loss as a symptom in particular has on these patients’ emotional and physical health. Almost two‐thirds of the mTBI participants reported tinnitus, which was a significantly higher proportion than in the control group, who had a tinnitus prevalence of 16.4%, consistent with previous published rates found of the general population . Whereas all control participants scored within the slight to mild range on the THI, over one‐third of the mTBI group had a moderate to catastrophic classification, highlighting the increased level of disability in these patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In examining the severity of the symptoms captured using PROMs, over half of the mTBI participants who reported hearing loss had an HHIA sore classified as significant, emphasizing the impact hearing loss as a symptom in particular has on these patients’ emotional and physical health. Almost two‐thirds of the mTBI participants reported tinnitus, which was a significantly higher proportion than in the control group, who had a tinnitus prevalence of 16.4%, consistent with previous published rates found of the general population . Whereas all control participants scored within the slight to mild range on the THI, over one‐third of the mTBI group had a moderate to catastrophic classification, highlighting the increased level of disability in these patients.…”
Section: Discussionsupporting
confidence: 88%
“…Almost two-thirds of the mTBI participants reported tinnitus, which was a significantly higher proportion than in the control group, who had a tinnitus prevalence of 16.4%, consistent with previous published rates found of the general population. 40 Whereas all control participants scored within the slight to mild range on the THI, over one-third of the mTBI group had a moderate to catastrophic classification, highlighting the increased level of disability in these patients. Lastly, almost half of mTBI participants who complained of hyperacusis had clinically significant symptoms as determined by the HQ.…”
Section: Fig 4 (A) Percentage Of Mtbi Versus Controls Patients Withmentioning
confidence: 91%
“…Meikle and Griest (1989) suggested that “men exposed to long-duration occupational noise tend to report tinnitus that is in ‘both ears,’ while tinnitus that is due to illness or other non-noise-related causes tends to be localized in the head.” (p. 74) Vernon (1978) may have been the first to posit that tinnitus located within the head may be due to head injury. In a recent study (Henry et al, 2012), almost half of the participants with moderate to severe traumatic brain injury reported that their tinnitus was perceived “inside the head,” whereas only 8% of the participants without traumatic brain injury reported this same perception. If these findings of differential tinnitus location are repeated in further trials, then this could have implications regarding underlying mechanisms of tinnitus generation.…”
Section: Discussionmentioning
confidence: 97%
“…An example of telehealth for rehabilitation is tinnitus management for Veterans and military personnel with TBI [117]. Another example is the emerging use of remote monitoring devices to assess visual structure and function [118].…”
Section: New Technological Approaches Affecting Rehabilitationmentioning
confidence: 99%